ANALISIS DAN PERANCANGAN SISTEM PROMOSI BERBASIS WEB (STUDI KASUS : PADA EV-GARDEN) - Karman, Zulfi; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2018)
EV-Garden is an untapped restaurant full of information and communication technology. EV-Gardendoes not yet have a website that can support packages and facilities available at EV-Garden, with the EVGarden promotional site can be easier in terms of promotional packages and facilities available, whichcan be better known to jambi people about the packages and facilities available at EV-Garden. DesigningWeb-Based Promotion System In this EV-Garden using PHP programming language and using objectbased modeling techniques to view system analysis and design, that is in the form of use case diagrams,class diagrams, and activity diagrams. Results from this study. EV - Garden Technique. For furtherresearch can be equipped with other data management, such as GIS and Live Chat features with systemsthat integrate with existing systems in EV-Garden.